Analysis of Environmental Conditions in Red-Eyed Snail Silvofishery in Buruk Bakul Village - Simangunsong, Gusnar; Budijono, Budijono; Fauzi, Muhammad (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Buruk Bakul Village has a mangrove distribution covering approximately 168 hectares. However, coastal abrasion, which reaches an average of 4 meters per year, directly impacts biodiversity, including a decline in gastropod populations due to loss of shelter and food sources. One affected species is the red-eyed snail (Cerithidea obtusa), which plays a vital role in the food chain of coastal ecosystems. This study aims to determine the practice of silvofishery on C. obtusa and environmental quality, as well as changes in environmental quality due to silvofishery practices. Sampling technique: Sampling was done using the stratified random sampling method. The results showed that Silvofishery practices integrating mangrove conservation with red-eyed snail cultivation in Buruk Bakul Village showed varying results depending on environmental conditions. Plot 3 recorded the best growth with a length of 1.22 cm and a weight of 1.91 g, which was supported by the fine mud substrate and high organic matter content. In contrast, plot 1 showed the lowest results with a length of 0.77 cm and a weight of 0.48 g. Environmental conditions such as soil pH, temperature, and organic matter significantly influence snail growth, with soil pH and temperature as the dominant factors.